Synthesis and crystal structures of novel copper(II) complexes with glycine and substituted phenanthrolines: reactivity towards DNA/BSA and in vitro cytotoxic and antimicrobial evaluation - Inci, Duygu; Aydin, Rahmiye; Vatan, Ozgur; Sevgi, Tuba; Yilmaz, Dilek; Zorlu, Yunus; Yerli, Yusuf; Cosut, Bunyemin; Demirkan, Elif; Cinkilic, Nulufer (SPRINGER, 2017)
New copper(II) complexes-dimeric-[Cu(nphen)(gly)(H2O)](+) (1) and [Cu(dmphen)(gly)(NO3)(H2O)] (2) (nphen = 5-nitro-1,10-phenanthroline, dmphen = 4,7-dimethyl-1,10-phenanthroline, and gly = glycine)-have been synthesized and characterized by CHN analysis, single-crystal X-ray diffraction techniques, FTIR, EPR spectroscopy, and cyclic voltammetry. The CT-DNA-binding properties of these complexes have been investigated by thermal denaturation measurements and both absorption and emission spectroscopy. The DNA cleavage activity of these complexes has been studied on supercoiled pUC19 plasmid DNA by gel electrophoresis experiments in the absence and presence of H2O2. Furthermore, the interaction of these complexes with bovine serum albumin (BSA) has been investigated using absorption and emission spectroscopy. The thermodynamic parameters, free-energy change (Delta G), enthalpy change (Delta H), and entropy change (Delta S) for BSA + complexes 1 and 2 systems have been calculated by the van't Hoff equation at three different temperatures (293.2, 303.2, and 310.2 K). The distance between the BSA and these complexes has been determined using fluorescence resonance energy transfer (FRET). Conformational changes of BSA have been observed using the synchronous fluorescence technique. In addition, in vitro cytotoxicities of these complexes on tumor cell lines (Caco-2, A549, and MCF-7) and healthy cells (BEAS-2B) have been examined. The antimicrobial activity of the complexes has also been tested on certain bacteria cells. The effect of mono and dimeric in the above complexes is presented and discussed. New copper(II) complexes-dimeric-[Cu(nphen)(gly)(H2O)](+) (1) and [Cu(dmphen)(gly) (NO3)(H2O)] (2) (nphen = 5-nitro-1,10-phenanthroline, dmphen = 4,7-dimethyl-1,10-phenanthroline and gly = glycine)-have been synthesized and characterized by CHN analysis, single-crystal X-ray diffraction techniques, FTIR and EPR spectroscopy. They have been tested for their in vitro DNA/BSA interactions by the spectroscopic methods. These complexes exhibited higher cytotoxic and antimicrobial activities. Complex 1 shows better DNA / BSA interactions in comparison to complex 2.
Keywords: Copper(II); Substituted phenanthrolines; Glycine; Single-crystal X-ray diffraction; DNA/BSA interactions; Cytotoxicities; Antimicrobial activities; DNA-BINDING PROPERTIES; OXIDATIVE CLEAVAGE ACTIVITY; HUMAN SERUM-ALBUMIN; SCHIFF-BASE; ANTIOXIDANT ACTIVITY; PROMOTED HYDROLYSIS; PHOSPHATE DIESTERS; ANTITUMOR-ACTIVITY; TERNARY COMPLEXES; METAL-COMPLEXES; Biochemistry & Molecular Biology; Chemistry